The Effect Of Financial Performance And Firm Size On Firm Value (Case Study of Banking Companies Listed on the Indonesia Stock Exchange in 2018-2020) - Adevia Yulia Rahima; Dul Muid (DIPONEGORO UNIVERSITY, 2023)
The goal of this study is to determine the correlation between Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), Return on Assets (ROA), and Firm Size to Firm Value in the banking sector listed on the Indonesia Stock Exchange in 2018–2020. An IDX-listed banking company for the years 2018 to 2020 serves as the study's sample. Using the SPSS Release 23 application, multiple linear regression is used as the analytic method. The findings of this study suggest that Return on Asset (ROA) and Loan to Deposit Ratio (LDR) substantially impact firm value. Otherwise, Non-Performing Loans (NPL) and Firm Size have little impact on the firm value.